THE STRATEGY OF SELF-DISCLOSURE BY WARDAH IN BRAND COMMUNICATION ON SOCIAL MEDIA - Istiqomah (PT. Antis International Publisher, 2026)
Objective: This study aims to explore Wardah's self-disclosure strategy in brand communication on social media, focusing on how it fosters trust and loyalty, particularly among the younger generation. Method: A qualitative approach was employed, using discourse analysis of Wardah's social media content and in-depth interviews with young consumers of Wardah products. Results: The findings reveal that Wardah effectively utilizes self-disclosure to create emotional connections with its audience, enhancing both trust and loyalty. Various narrative types, such as personal stories and behind-the-scenes content, were identified as key tools in this process. Novelty: This research offers new insights into the application of Social Penetration Theory and Relationship Management Theory in digital marketing, specifically within the context of brand communication strategies targeting younger audiences. The study highlights the role of authentic and personal narratives in building long-term relationships between brands and consumers in the digital age.